PENERAPAN PEMENUHAN KEWAJIBAN REHABILITASI MEDIS DAN REHABILITASI SOSIAL TERHADAP PENYALAHGUNAAN NARKOTIKA - Afpryanto Sihaloho; Ade Adhari (UNES Law Review, 2023)
This study aims to analyze the application of medical rehabilitation and social rehabilitation for narcotics abusers in Palu. This study uses normative research methods because the existing problems will be examined by taking into account the principles of law and applicable laws and regulations, then analyzing and making answers to the problems to be discussed. The results of the study show that in practice law enforcement in narcotics crime cases, Article 112 paragraph (1) of the RI Law is often applied. 35 of 2009 to addicts, abusers, and victims of narcotics abuse. Against the two perpetrators, namely Al Ayudi Parhan and Ridwan, are narcotics abusers who should have the opportunity to be subject to sanctions in the form of medical rehabilitation and social rehabilitation because they are in accordance with the classification of narcotics crimes in SEMA No. 04 of 2010, namely based on the weight of evidence of narcotics when caught red-handed by investigators from the National Police or BNN, a positive laboratory test letter using narcotics, and there is no evidence that the person concerned is involved in illicit narcotics trafficking.